ANSWER
[-4,5]
STEP BY STEP EXPLANATION
ok, so first you plug in the equation 3x+20 into the y in the equation x^2+2x
Your new equation should be 3x+20=x^2+2x
Then you subtract 2x from both sides and your new equation should be x+20=x^2
Then you subtract 20 and x from both sides and your new equation should be 0=x^2-x-20
Then you multiply a with c, which is -20 and then you get b, which is -x or -1. After that you have to find two numbers that is the product of -20 and the sum of -1, which is -5 and 4
Then it would be (x-5)(x+4)=0. You you add 5 to both sides which will be x=5 and then you subtract 4 from both sides, which will be x=-4
Then your final answer is [-4,5]
hope this helped!